A BODIPY-based mitochondria-targeted turn-on fluorescent probe with dual response units for the rapid detection of intracellular biothiols. (May 2018) - Wang, Fang-Fang; Liu, Yu-Jiao; Wang, Bei-Bei; Gao, Lian-Xun; Jiang, Feng-Lei; Liu, Yi
Abstract: A novel reaction-based turn-on fluorescent BODIPY probe for the detection of biothiols was designed and synthesized. The sensitivity and selectivity of the probe were greatly enhanced by introduction of dual reactive groups, which simultaneously acted as fluorescence quenching units. The probe had fluorescence enhancement of up to 106-fold, 56-fold and 77-fold in the presence of Hcy, Cys and GSH, respectively. This probe had stable fluorescence emission within physiological pH range and exhibited low cytotoxicity. The background of the probe was quite low and medium wash was not required in cell imaging. This probe could rapidly image intracellular biothiols in ca. 10 min, and selectively accumulated in mitochondria. Graphical abstract: This fluorescent probe is no background and can stain intracellular thiols in 10 min. Highlights: A dual activated fluorescent sensor for biothiols is described. Neither background fluorescence nor medium wash is required. Quick staining of intracellular thiols is noted. Selective accumulation of probe in mitochondria.